Treatment with Recombinant Human MG53 Protein Increases Membrane Integrity in a Mouse Model of Limb Girdle Muscular Dystrophy 2B - Gushchina, Liubov V. (Mol Ther, 2017)
Limb girdle muscular dystrophy type 2B (LGMD2B) and other dysferlinopathies are degenerative muscle diseases that result from mutations in the dysferlin gene and have limited treatment options. The dysferlin protein has been linked to multiple cellular functions including a Ca(2+)-dependent membrane repair process that reseals disruptions in the sarcolemmal membrane. Recombinant human MG53 protein (rhMG53) can increase the membrane repair process in multiple cell types both in vitro and in vivo. Here, we tested whether rhMG53 protein can improve membrane repair in a dysferlin-deficient mouse model of LGMD2B (B6.129-Dysf(tm1Kcam)/J). We found that rhMG53 can increase the integrity of the sarcolemmal membrane of isolated muscle fibers and whole muscles in a Ca(2+)-independent fashion when assayed by a multi-photon laser wounding assay. Intraperitoneal injection of rhMG53 into mice before acute eccentric treadmill exercise can decrease the release of intracellular enzymes from skeletal muscle and decrease the entry of immunoglobulin G and Evans blue dye into muscle fibers in vivo. These results indicate that short-term rhMG53 treatment can ameliorate one of the underlying defects in dysferlin-deficient muscle by increasing sarcolemmal membrane integrity. We also provide evidence that rhMG53 protein increases membrane integrity independently of the canonical dysferlin-mediated, Ca(2+)-dependent pathway known to be important for sarcolemmal membrane repair.